Renewable Energy, Innovation and Adaptation to Climate Change: Evidence from Europe and Central Asia - Dekhkanova, Nargiza; Azimova, Dilafruz; Akhunova, Elena; Saitov, Elyor; Tosheva, Shahnoza; Salahodjaev, Raufhon (International Journal of Energy Economics and Policy, 2025)
The aim of this research is to examine the effect of renewable energy consumption and innovation on adaptation to climate change in Europe and Central Asia over the period 2000-2021. In this study, we use several panel data methods such as fixed effects method, two step system GMM estimator and panel corrected standard errors estimator to account for endogeneity, simultaneity and cross-sectional dependence. Our results show that renewable energy has overall positive link with adaptation to climate change, proxied by ND Gain index. We also document that innovation measured by number of patents has positive effect on ND Gain index in Europe and Central Asia. We conduct robustness tests by including additional socio-economic variables. The results remain robust. The study offers policy implications and suggests avenue for future research.